Daddy Pig's Old Chair - Barker, Cicely Mary (UK Ladybird Books Ltd, 2012)
Naughty Mummy Pig has given Daddy Pig's favourite old chair to the jumble sale! How is he ever going to get it back?
Shelving Location Playgroup Class. Fiction Book Section
Keywords: English Fiction Book